Prosthetic management of hard palate perforation in a child with acute lymphoblastic leukemia - Gunjan C Chouksey; Kanchan P Dholam (Indian Journal of Medical and Paediatric Oncology)
Palatal perforation is an uncommon complication seen in children with acute lymphoblastic leukemia undergoing chemotherapy. This may impact basic functions, such as speech, swallowing, chewing, affecting the quality of life (QOL). Prosthetic rehabilitation of the palatal perforation with obturator can optimally restore function, thereby improving and enhancing the QOL of these patients.